Identification of a New Susceptibility Locus for Systemic Lupus Erythematosus on Chromosome 12 in Individuals of European Ancestry. Issue 1 (January 2016) - Demirci, F. Yesim; Wang, Xingbin; Kelly, Jennifer A.; Morris, David L.; Barmada, M. Michael; Feingold, Eleanor; Kao, Amy H.; Sivils, Kathy L.; Bernatsky, Sasha; Pineau, Christian; Clarke, Ann E.; Ramsey‐Goldman, Rosalind; et al.
Abstract : Objective: Genome‐wide association studies (GWAS) in individuals of European ancestry identified a number of systemic lupus erythematosus (SLE) susceptibility loci using earlier versions of high‐density genotyping platforms. Followup studies on suggestive GWAS regions using larger samples and more markers identified additional SLE loci in subjects of European descent. This multistage study was undertaken to identify novel SLE loci. Methods: In stage 1, we conducted a new GWAS of SLE in a North American case–control sample of subjects of European ancestry (n = 1, 166) genotyped on Affymetrix Genome‐Wide Human SNP Array 6.0. In stage 2, we further investigated top new suggestive GWAS hits by in silico evaluation and meta‐analysis using an additional data set of subjects of European descent (>2, 500 individuals), followed by replication of top meta‐analysis findings in another data set of subjects of European descent (>10, 000 individuals) in stage 3. Results: As expected, our GWAS revealed the most significant associations at the major histocompatibility complex locus (6p21), which easily surpassed the genome‐wide significance threshold ( P < 5 × 10 −8 ). Several other SLE signals/loci previously implicated in Caucasians and/or Asians were also confirmed in the stage 1 discovery sample, and the strongest signals were observed at 2q32/ STAT4 ( P  = 3.6 × 10 −7 ) and at 8p23/ BLK ( P  = 8.1 × 10 −6 ). Stage 2 meta‐analyses identified a new genome‐wide significant SLE locus at 12q12 (meta P  = 3.1 × 10 −8 ), which was replicated in stage 3. Conclusion: Our multistage study identified and replicated a new SLE locus that warrants further followup in additional studies. Publicly available databases suggest that this newly identified SLE signal falls within a functionally relevant genomic region and near biologically important genes.